Geochemical and isotopic tracing of salinity loads into the Ramsar listed Verlorenvlei freshwater estuarine lake, Western Cape, South Africa - Sigidi, Nthabeliseni Thendo (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.